Investment Protection Along the Belt and Road - Kher, Priyanka; Tran, Trang (World Bank, Washington, DC, 2019)
This paper examines the level of investment protection for selected countries along the Belt &Road Initiative (BRI), based on coding the textual content of 17 investment laws and 648international investment agreements (IIAs). We find substantial heterogeneity in the levels ofprotection provided in the reviewed laws and IIAs, and consequently along the same BRI corridorsand projects. Moreover, the current lack of effective enforcement – as shown by past treatyviolations and lack of efficient domestic court systems – poses an additional layer of risk forinvestors. Substantive improvements and harmonization in standards of treatment and recoursemechanisms in these legal instruments can help reduce investment risks. Given the scale of plannedinvestments, to minimize dispute risks, BRI governments will need to ensure full understandingof their law and treaty commitments and strengthen the capacity to enforce them.